Meal-kit delivery services : a flash in the pan or a cooking tradition in the making? - Harden, Gina; Allen, Charlotte, active 2023 (London : SAGE Publications: SAGE Business Cases Originals, 2023)
Leila, a former executive in a tech payment system startup firm, is contemplating the next stage in her professional career. After taking some time off to be with her family, she is ready to start her next venture and is looking to invest in another technology-driven business. Leila enjoys the culinary arts and had a positive experience with Blue Apron, the meal-kit delivery service. This has Leila contemplating a foray into the meal-kit delivery service arena. Meal-kit industry revenue is expected to grow to over USD 7.6 billion in 2024 (Conway, 2020). Many, once reluctant to try this innovative service, entered the digital food domain during the global pandemic that began in 2020. However, Leila realizes it is still an early-adopter market with many unique segments, appealing to a diverse variety of consumers with a focus on fresh meals and, more importantly, those with discretionary funds to afford the higher prices of most prepackaged meal kits. This case examines the meal-kit delivery industry from the perspective of a business executive contemplating a new venture, by either investing or creating her own startup, in that space. The impact of competitive, economic, technological, and social forces on both the industry and consumers are addressed.
Description based on XML content.
Keywords: elektronické knihy; electronic books; New business enterprises -- Case studies; Delivery of goods -- Case studies